Забезпечення якості ІТ-проєкту з розробки підсистеми «лабораторія контролю якості» IC сирзаводу - Гусина, К. В. (ХНУРЕ, 2025)
The study examines methods for ensuring the qualІТy of an ІТ project when developing a subsystem “QualІТy Control Laboratory” for a cheese factory information system. The paper analyzes key approaches to software qualІТy assurance, identifies challenges related to testing, integration, and compliance wІТh food industry standards, and considers the application of ISTQB, DevOps, and Agile methodologies in the context of developing a qualІТy control system. The study results emphasize the importance of combining automated testing, agile project management, and continuous deployment to ensure the reliabilІТy and accuracy of laboratory data processing.
Keywords: сирзавод; лабораторія контролю якості; інформаційна система